Origin and Growth of Urban Centers: A Study of Pokhara Metropolitan City, Nepal - Poudel, Khagendra Raj (The Himalayan Geographers, 2025)
This research examines the origin and growth of Pokhara Metropolitan City within the broader framework of urbanization in Nepal. The study aims to analyze how historical, geographical, political, and socio-economic factors have shaped Pokhara’s transformation from a small trade settlement into a major urban center. It focuses on administrative expansion, population growth, and infrastructure development across different political regimes. A qualitative case study method was employed, using historical records, census data (1961–2021), policy documents, and academic literature. Spatial and demographic analyses were conducted to trace changes in municipal boundaries, ward distribution, and population density over time. Findings highlight that Pokhara’s urban development has been driven by its strategic location in the Himalayan foothills, proximity to eight lakes (especially Phewa and Begnas), the construction of highways and an international airport, the growth of tourism, and political restructuring. The city’s evolution from municipality in 1962 to metropolitan status in 2017 reflects the combined influence of natural geography, migration, infrastructure, and decentralization policies. This study contributes to understanding the drivers of urban growth in Nepal and provides relevant insights for planners and policymakers addressing the challenges and opportunities of rapidly expanding secondary cities.